STUDENTS’ PERCEPTIONS ON THE TEACHER USING L1/L2 IN TEACHING EFL CLASS - Sumiati Sumiati; Amir Hamzah (EEAL Journal (English Education and Applied Linguistics Journal), 2021)
This study aimed to find out students’ perceptions on the teacher using L1/L2 in teaching EFL Class. It employed a qualitative research which used case study. The participants of this study were three students with categories advance, intermediate, and low. The data were collected by using in-dept interview. The items for the interview were developed from the previous research Elmetwally (2012) which were found appropriate to be used. The findings revealed that the use of Indonesian language in the EFL Class are generally positive. The three participants stated that they prefered when learning with the teachers used of L1/L2 in teaching EFL Classroom e.g explaining the material, explaining difficult vocabulary, translating and presentation. In addition, the students’ perceptions has a different percentage of used L1/L2 in EFL Class. The participants with Advance category stated that she was needed 50% Indonesian explanations when explaining materials, giving examples, explaining formulas and theories. Then, she was needed 50% the full English explanations when the teacher greeting and opening the lessons, checking attendance, giving assignments, correcting students mistakes, closing the lessons, giving homework, and announcing grades. Meanwhile, the intermediate students’ stated that she was needed a full English explanations as much as 45% and needed to be used when explaining the materials, and the rest 55% was needed on the Indonesian explanations to clarify the materials that was explained using English earlier. Furthermore, the low students’ stated that she was needed as much as 80% for Indonesia explanations for explaining the material more deeply so that students become more understand. And the rest 20% was needed for English explanations in opening and closing the teaching activity, and giving an assignment so that the students would get used to it. Moreover, it can be concluded that the use of L1/L2 as a facilitator in their learning, as a tool to help them get a better understanding when learning English.